Layout of Urban Distribution Center Using Possibilistic Programming - Demirtas, Nurgul; Tuzkaya, Umut R.; Tanyas, Mehmet (ATLANTIS PRESS, 2016)
Distribution centers, link supply chain to the customers. Layout of the distribution centers is very important in terms of product conservation at the required service level and delivering of products with minimum cost to the customer from distribution centers. Therefore, the layout design of distribution centers should be handled with a smart decision system. In this study, the layout design of a fruits and vegetable hall, which is a kind of urban distribution center, is investigated for two different scenarios: (1) assignments of the brokers to the stores and (2) assignments of the products to the stores. The study suggests the most suitable allocation models for the inner layout of distribution center. In the first phase, the requirements of the mathematical model to develop the decision making system for the layouts of distribution center that will be determined. In the second phase, allocation models will be developed and solved for fruits and vegetables halls in Istanbul.
Keywords: City Logistics; Fruits and Vegetables Hall; Warehouse Design; Possibilictic Linear Programming; Linear Programming; LOGISTICS NETWORK DESIGN; LOCATION PROBLEM; MODEL; UNCERTAINTY; INVENTORY; Computer Science